Cybersecurity Education as an Effort to Improve Digital Literacy of Teachers and Students at SMAN 3 Polewali - Anugrayani Bustamin; Ady Wahyudi Paundu; Ingrid Nurtanio; Adnan .; Amil Ahmad Ilham; Muhammad Niswar; Muhammad Alief Fahdal Imran Oemar; Muhammad Aryandi; Randy Kamal Husein; Yusri Simang; Ahmad Ali Husein; Reyhan Fahreza; A. Tyas Nur Atda; Mutiara .; Ahmad Nur Alim (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
The rapid development of digital technology has increased the risk of cybersecurity threats, especially among students and educators. The lack of understanding regarding personal data protection, digital account security, and the threat of phishing and malware is a challenge that needs to be addressed through structured educational activities. This community service activity aims to improve digital literacy and cybersecurity awareness for teachers and students at SMAN 3 Polewali through interactive, gamification-based training using the Interland by Google platform. The implementation method is carried out in three stages: preparation and identification of needs, training implementation, and activity evaluation using pre-tests and post-tests based on Google Forms. The material provided includes personal data protection, password security, OTP security, awareness of phishing and malware, and the risks of using public Wi-Fi. The evaluation results showed an increase in participants' understanding of most indicators related to digital security. Based on the results of the pre-test and post-test on 41 participants, there was an increase in most indicators of digital security literacy. The highest improvement was in public Wi-Fi security (63% to 73%), followed by personal data protection (65% to 73%), handling cyberbullying (53% to 58%), and password security (85% to 87%). Meanwhile, OTP security remained at 100% in both phases, indicating excellent participant awareness from the start of the program.